Meningkatkan Hasil Belajar PPKn Melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) pada Peserta Didik Kelas VII-3 di SMPN 1 Kecamatan Pinggir Kabupaten Bengkalis Tahun Pelajaran 2022/2023 - Muryati, Desi; Sari, Mila Nirmala; Idris, Budi (CIVITAS (JURNAL PEMBELAJARAN DAN ILMU CIVIC), 2024)
ABSTRACTUniversities, as institutions of higher education, play an important role in shapingsociety and producing future leaders. One of the increasingly popular approaches tohigher education management is peaceful values-based higher educationmanagement. The purpose of this study is to thoroughly analyze various articles,literature, and research reports related to the application of this approach. The resultsshow that however, the research also points out many important opportunities, suchas building an inclusive learning environment, building more moral leaders, andimproving the public perception of the college. In addition, the research shows howimportant the integration of peaceful values in the higher education curriculum andcross-sectoral cooperation are. This research provides important information forhigher education leaders, educational practitioners, and policy makers to makeuseful plans to face challenges and capitalize on opportunities to implement peacefulvalues-based higher education management, which can have a positive impact onsociety and the nation as a whole.Keyword: Challenges, Opportunities, Higher Education Management, PeacefulValues—————————— ◆ ——————————